Development of Learning Media for Motorcycle Chassis Training Kit - Handoyono, Nurcholish Arifin (Universitas Ahmad Dahlan, 2021)
This research aims to determine the development process and the feasibility of learning media for motorcycle chassis training kit at SMK Muhammadiyah 1 Bambanglipuro. The type of research used is R&D. The research subjects were 32 students of class X TBSM SMK Muhammadiyah 1 Bambanglipuro. The data collection instruments used observation and questionnaires. The data analysis technique used the evaluation criteria analysis to determine the feasibility of learning media. The results showed that: (1) The development process went through several stages, namely: (a) problem background; (b) problem identification; (c) development ideas; (d) pre-production stage (tools and materials); (e) production stage; (f) product development; (g) validation and revision; (h) feasibility test; and (i) wearable products; and; (2) Learning media for motorcycle chassis training kit are categorized as very suitable for use in learning with the results of validation of media experts by 90%, material experts by 95%, small group trial of 85.24%, and large group trial of 83.94%.